Ảnh hưởng của quản trị doanh nghiệp và đa dạng hóa ngân hàng đến sự ổn định của ngân hàng thương mại Việt Nam: Ước lượng SYS-GMM - Nguyễn Trung, Dũng; Lê Hải, Trung; Nguyễn Thanh, Phương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The purpose of this paper is to apply systematic generalized method of moments (SYS-GMM) regression model to evaluate the impact of corporate governance and bank diversification (including income and asset diversification) on the stability of 26 Vietnamese commercial banks over the period of 2011–2022. The results indicate that income and asset diversification are negatively correlated with the banks' Z-score. In contrast, factors such as the board size, the number of female board members, the number of general directors, state ownership percentage, and foreign ownership percentage positively influence the stability of Vietnamese commercial banks. However, the number of independent board ownership and the board ownership do not contribute to enhancing the banks' risk management efficiency. Additionally, corporate governance mechanisms strengthen the impact of asset diversification on the stability of commercial banks, which is a noteworthy finding of this study. The authors propose several policy implications for improving corporate governance, income diversification, and asset diversification to enhance the stability of Vietnamese commercial banks.
Keywords: SYS-GMM; Bank stablility; Asset diversification; Income diversification; Bank diversification; Corporate governance